Impacts of the Affordable Care Act on Community Health Centers: Characteristics of New Patients and Early Changes in Delivery of Care. Issue 4 (October 2018) - Hatch, Brigit; Smith, Ning; McBurnie, Mary Ann; Quach, Thu; Mayer, Kenneth H.; Dunne, Mary J.; Cottrell, Erika
Abstract : The aim of this study was to assess the impact of the Affordable Care Act (ACA) on community health centers (CHCs). Using electronic health records from the Community Health Applied Research Network, we assessed new patient characteristics, office visit volume, and payer distribution among CHC patients before and after ACA implementation, 2011-2014 (n = 442 455). New patients post-ACA were younger, more likely to be female and have chronic health conditions, and utilized more primary care ( P < .05 for each). Post-ACA, clinics delivered 19% more office visits and more visits were reimbursed by Medicaid. The support of CHCs is needed to meet increased demand post-ACA.